On inequalities for the norms of intermediate derivatives of multiply monotone functions defined on a finite segment - Skorokhodov, D.S. (Український математичний журнал, 2012)
We study the following modification of the Landau–Kolmogorov problem: Let k; r ∈ ℕ, 1 ≤ k ≤ r − 1, and p, q, s ∈ [1,∞]. Also let MM^m, m ∈ ℕ; be the class of nonnegative functions defined on the segment [0, 1] whose derivatives of orders 1, 2,…,m are nonnegative almost everywhere on [0, 1]. For every δ > 0, find the exact value of the quantity We determine the quantity in the case where s = ∞ and m ∈ {r, r − 1, r − 2}. In addition, we consider certain generalizations of the above-stated modification of the Landau–Kolmogorov problem.